2006
DOI: 10.1002/ana.20761
|View full text |Cite
|
Sign up to set email alerts
|

SEPN1: Associated with congenital fiber‐type disproportion and insulin resistance

Abstract: SEPN1 is the second genetic cause of CFTD and the first cause of autosomal recessive CFTD to be identified to our knowledge. CFTD is the fourth clinicopathological presentation that can be associated with mutations in SEPN1. Insulin resistance may be a specific, previously unrecognized aspect of SEPN1-related myopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(77 citation statements)
references
References 15 publications
2
75
0
Order By: Relevance
“…This condition, however, is genetically heterogeneous and has been observed in several forms of congenital myopathies, neuromuscular disorders, and muscular dystrophies (Clarke and North 2003). Mutations in ACTA1 (Laing et al 2004), SEPN1 (Clarke et al 2006), TPM3 (Clarke et al 2008), RYR1 (Wilmshurst et al 2010), and more recently MYH7 (Ortolano et al 2011) have also been identified in patients with FTD. To add to its nonspecific nature, this morphological finding has been reported in association with several inherited metabolic disorders including Pompe disease (Martin et al 1976), multiple sulfatase deficiency (Tachi et al 1984), congenital lactic acidosis (Iso et al 1993), metachromatic leukodystrophy (Krendel et al 1994), carnitine palmitoyltransferase deficiency (Shintani et al 1995), and Krabbe disease (Marjanovic et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…This condition, however, is genetically heterogeneous and has been observed in several forms of congenital myopathies, neuromuscular disorders, and muscular dystrophies (Clarke and North 2003). Mutations in ACTA1 (Laing et al 2004), SEPN1 (Clarke et al 2006), TPM3 (Clarke et al 2008), RYR1 (Wilmshurst et al 2010), and more recently MYH7 (Ortolano et al 2011) have also been identified in patients with FTD. To add to its nonspecific nature, this morphological finding has been reported in association with several inherited metabolic disorders including Pompe disease (Martin et al 1976), multiple sulfatase deficiency (Tachi et al 1984), congenital lactic acidosis (Iso et al 1993), metachromatic leukodystrophy (Krendel et al 1994), carnitine palmitoyltransferase deficiency (Shintani et al 1995), and Krabbe disease (Marjanovic et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…later, they 189 also demonstrated homozygous sePN1 deletion in patients with CMD with Mallory body-like inclusions. Finally Clarke et al 190 described sePN1mutations in two sisters with a diagnosis of typical congenital fiber-type disproportion without minicore lesions or dystrophic changes. Therefore the spectrum of selenoprotein-related disorders includes rigid spine CMD, multiminicore myopathy, desmin-related myopathy with Mallory body-like inclusions and congenital fiber-type disproportion.…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…The mutation in the genes ACTA1 (22), SEPN1 (48) or TPM3 (23) express the morphological and histochemical alteration in CFTD (49). Since the first description of this disease, approximately 67 cases have been described (16), but just a few cases originally in Brazil (50).…”
Section: Applicability Of P-mfm In Family With Cftd Associated Musclmentioning
confidence: 99%
“…This condition could happen due to hypotrophy of type 1 fibres found in the respiratory muscles, including the diaphragm (14,16,20,22,48,49) or as a result of severe kyphoscoliosis, which progressively diminished lung capacity. Thus, it is important that patients be monitored for maintenance of a postural alignment and breathing function.…”
Section: Applicability Of P-mfm In Family With Cftd Associated Musclmentioning
confidence: 99%